THE ROLE OF THE NURSE IN THE INCLUSION OF THE MENTALLY PAID IN PRIMARY HEALTH CARE: HE ROLE OF THE NURSE IN THE INCLUSION OF THE MENTALLY PAID IN PRIMARY HEALTH CARE (REMUNOM, 2023)
AbstractCurrently, the Family Health Strategy (ESF), a Primary Health Care (PHC) action, which is the user's gateway, faces the challenges of offering completeness in health, considering the complexity of the life of a user with this disorder mental. For this reason, the present study aimed to verify the role of the nurse in Primary Health Care in order to work on strengthening family and community ties in the inclusion of the mentally ill in society. With the following specific objectives: to identify which actions are aimed at strengthening family and community ties, verify the functionality of the user's psychosocial care network, understand which basic health rights are required, guarantee them, in addition to developing established actions in public policies, identifying the user care network. The research was based on a qualitative methodology, in which the analysis of the selected works was carried out through a bibliographical review, with the purpose of investigating and describing the role of the nurse in the inclusion of the mentally ill in primary care. For that, we tried to clarify the importance of the nurse and the entire health team together with the support networks in the reception for the inclusion of the mentally ill in the Basic Health Units. In the end, it was considered that the nurse has a fundamental role in basic health care regarding the inclusion of the mentally ill user. Thus, it should be noted that nursing care needs to be improved and humanized in terms of providing care to this user using the guidelines that permeate the National Primary Care Policy and its support network.